Effects of weaning age on costs and revenue in three-site production - Main, R.G.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were completed to determine the effects of weaning age on growing pig costs and revenue within a three-site production system. Cost and revenue were measured by applying operationally dependant information to trial data. Economic effects were determined assuming either limited or nonlimited finishing capacity. In both trials and finishing capacity scenarios (limited or nonlimited), income over costs and cost per hundredweight improved linearly as weaning age increased. In these studies, increasing weaning age up to 21.5 days resulted in linear increases in weaned pig value within a three-site production system. Assessing a common value to acceptable quality wean pigs regardless of weaning age or weight, may lead to false conclusions concerning a breeding herd’s true financial performance.
Keywords: Weaning age; Costs; Revenue; Economics; Swine